Fatores que interferem no nível de qualidade de vida no trabalho segundo a percepção dos trabalhadores: estudo de caso em um hospital de trauma - Rocha, Lenilson Olinto (2017)
Hospitals group workers of various functions and need specific demands for each type of function that is exercised, which is why evaluating the QWL of a hospital environment can contribute to the management of the organization to develop policies that promote satisfaction in the work environment and consequently an employee well-being and better health services for patients seeking care there. This dissertation identifies the factors with more influence the perception of the QWL level of the employees of different functions of a Trauma Hospital. The research was carried out with the workers of Hospital, grouped in 15 distinct functions, in a sample of 256 individuals. Data collection was performed by means of: observational plan with a structured script, a questionnaire with 34 variables based on the readjustment of the Walton QWL model (1973) by Timossi et al. (2009) and 6 sociodemographic variables. Data analysis techniques are based on descriptive analysis and factor analysis. The general conditions of work were classified as unsatisfactory, about 19 variables of QWL obtained a perception of satisfaction or positive and 15 with perception of dissatisfaction or negative, in addition, dimension 1 (adequate and fair compensation) showed to be more expressive in the perception of worker dissatisfaction, followed by dimension 4 (growth and security). The factor analysis found 10 latent factors, from the proposed QWL model, with total explained variance of 65.140%, and Factor 1 (Capacity Development and Legal Obligations) represented the greatest influence on the perception of QWL of the employees with 22.174% of the total variance explained. In the assessment of factor scores by office, radiology technical, physiotherapists and kitchen assistants (cupbearers and cooks) obtained the highest levels of dissatisfaction, and management positions obtained the highest rates of job satisfaction. Reliability was measured by the cronbach alpha and achivied 0.800. It is concluded, therefore, that the perception of QWL of Trauma Hospital employees is influenced by sociodemographic variables and the job that is exercised, and most workers perceive with dissatisfaction the remuneration, growth and professional development policy adopted at the Trauma Hospital.